The Impact of Artificial Intelligence (AI) on the Future of Jobs in Computer Science and Information Systems: A Systematic Literature Review - Heny Pratiwi; Muhammad Ibnu Sa'ad (Penelitian dan Pengembangan Ilmu, 2024)
The evolution of artificial intelligence (AI) in the fields of Computer Science and Information Systems has become a major research focus in recent decades. This research aims to investigate the impact of AI on job distribution and employment inequality in the context of Computer Science and Information Systems. The research method used is a systematic literature review, by collecting and analyzing relevant articles from reputable international databases. The results of the discussion show that the evolution of AI has brought significant changes in various aspects of work and influenced the division of tasks between humans and machines. The implication of this research is the importance of paying attention to the impact of AI in designing policies, training programs, and initiatives to minimize employment gaps and ensure fair access to employment opportunities in the AI ​​era.